2016
DOI: 10.3389/fphar.2016.00012
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum-Effect Relationships Between Chemical Fingerprints and Antibacterial Effects of Lonicerae Japonicae Flos and Lonicerae Flos Base on UPLC and Microcalorimetry

Abstract: The traditional Chinese medicines Lonicerae Japonicae Flos (LJF, Jinyinhua in Chinese) and Lonicerae Flos (LF, Shanyinhua in Chinese) refer to the flower buds of five plants belonging to the Caprifoliaceae family. Until 2000, all of these were officially listed as a single item, LJF (Jinyinhua), in the Chinese Pharmacopoeia. However, there have recently been many academic controversies concerning the separation and combination of LJF and LF in administrative regulation. Till now there has been little work comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…According to 'Ben Cao Gang Mu' (AD 1552-1578, the herbalism masterpiece which was known as the ancient Chinese encyclopedia, JYH was described as a commonly used herb to treat fever, phyma and sore. Modern pharmacological study has confirmed the antiviral, antibacterial and anti-inflammatory activities of JYH, supporting the traditional applications (Kang et al 2004;Kao et al 2015;Shi et al 2016). Likewise, pharmacological study showed antioxidative, anti-tumour, liver protective and hypoglycemic activities of JYH Kong et al 2017;Park et al 2012a).…”
Section: Introductionmentioning
confidence: 66%
“…According to 'Ben Cao Gang Mu' (AD 1552-1578, the herbalism masterpiece which was known as the ancient Chinese encyclopedia, JYH was described as a commonly used herb to treat fever, phyma and sore. Modern pharmacological study has confirmed the antiviral, antibacterial and anti-inflammatory activities of JYH, supporting the traditional applications (Kang et al 2004;Kao et al 2015;Shi et al 2016). Likewise, pharmacological study showed antioxidative, anti-tumour, liver protective and hypoglycemic activities of JYH Kong et al 2017;Park et al 2012a).…”
Section: Introductionmentioning
confidence: 66%
“…Spectrum–effect relationship analysis is an emerging approach to facilitating the bioactivity‐relevant quality control of herbal medicines. There is no doubt that the spectrum–effect relationship approach fits very well with the holistic mode of herbal medicines, eliciting the pharmacological efficacy via several components (Liu, Wu, Huang, Liu, & Feng, ; Shi et al, ; Zhang, Chen, Yang, & Shi, ). In the present study, we established a spectrum–effect relationship model to identify a set of combinatorial marker compounds that might be representative of the bioactivity of Cortex Mori, Ramulus Mori, Folium Mori and Fructus Mori.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, modern pharmacological research has discovered wide pharmacological actions, such as antiviral, anti‐inflammatory, antibacterial, antiendotoxin, antipyretic and antioxidative (Shang, Pan, Li, Miao, & Ding, ; Shi et al, ). Among these, the antioxidative activity makes a great contribution to its medicinal and edible value.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that a multivariate statistical mathematical model can be employed to create links between chemicals and efficacy, the combination of spectrum and effect by statistical analysis can provide a new route for target components. Shi et al () screened the major antibacterial components of chlorogenic acid and 3,4‐dicaffeoylquinic acid from Lonicerae Japonicae Flos and Lonicerae Flos by spectrum–effect relationships. Therefore, in this paper, a spectrum–effect relationship study between HPLC fingerprints and 1,1‐diphenyl‐2‐picrylhydrazyl (DPPH) radical scavenging activity of honeysuckle methanol extract was carried out for potential antioxidant compounds.…”
Section: Introductionmentioning
confidence: 99%